DA MEDICINA PREVENTIVA A MEDICINA COMUNITARIA: PROCESSO DE CONSTITUIÇÃO DE CAMPO DE ENSINO EXTRAMUROS NA FACULDADE DE MEDICINA DE BOTUCATU - UNESP (1969 - 1973) - Cyrino, Antonio Pithon [UNESP] (Associação Brasileira de Educação Médica, 2021)
An experience in using community as a space for medical education, conducted by the Department of Preventive Medicine - School of Medicine - Botucatu, SP, Brazil, is reported. The results of this new approach was evaluated by interviewing the staff of the Department and analyzing the pertinent documents. Changes were observed both, in experiences outside the hospital and within the Health Centers after the association of the principles of Community Medicine to those of Preventive Medicine. Such changes areclearly demonstrated by the specificity of the health services organized during the period of the study. In 1970, Sanitary Unit of Lageado was settled influenced by the concept of Preventive Medicine based on changes in altitudes and development of a preventive conscience in the medical students. The School Health Center settled in 1972, based of the principles of Community Medicine brought, new tendencies in relation to the previous experience. The focus of the project was changed from educational to technical and health care.

Estuda-se a experiência realizada na Faculdade de Medicina de Botucatu - UNESP, através do Departamento de Medicina Preventiva (DMP), ao constituir um novo espaço à educação médica: junto à comunidade. A investigação foi produzida através da análise de documentos e entrevistas com docentes do DMP. Identificou-se uma reorientação na constituição dos campos de ensino extramuros e prática em saúde ao incorporarem os pressupostos da Medicina Comunitária aos inicialmente adotados da Medicina Preventiva. Tal deslocamento é reconhecido pelas especificidades dos serviços de saúde organizados para tanto. Em 1970, instalou-se a “Unidade Sanitária do Lageado”: sob influência do ideário da Medicina Preventiva expresso nos objetivos de consecução de uma prática voltada à formação de atitudes e de uma consciência preventiva nos futuros profissionais. A constituição do Centro de Saúde Escola, em 1972, sob inspiração da Medicina Comunitária, imprimiu uma nova orientação a experiência anterior ao deslocar-se do ensino para a elaboração de um projeto técnico-assistencial.